2021
DOI: 10.1002/arch.21830
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Apis cerana zinc finger protein 41 gene and its involvement in the oxidative stress response

Abstract: Zinc finger proteins (ZFPs) are a class of transcription factors that contain zinc finger domains and play important roles in growth, aging, and responses to abiotic and biotic stresses. These proteins activate or inhibit gene transcription by binding to single‐stranded DNA or RNA and through RNA/DNA bidirectional binding and protein–protein interactions. However, few studies have focused on the oxidation resistance functions of ZFPs in insects, particularly Apis cerana. In the current study, we identified a Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Many ZNFs have been proven to be associated with biotic and abiotic stresses [65,66]. In Apis cerana, oxidative stress increased the expression of ZFP41 and the overexpression of this gene in vivo increased tolerance to oxidative stress [67]. This evidence provides a theoretical basis for further studying the function of ZNFs in stress resistance.…”
Section: Discussionmentioning
confidence: 79%
“…Many ZNFs have been proven to be associated with biotic and abiotic stresses [65,66]. In Apis cerana, oxidative stress increased the expression of ZFP41 and the overexpression of this gene in vivo increased tolerance to oxidative stress [67]. This evidence provides a theoretical basis for further studying the function of ZNFs in stress resistance.…”
Section: Discussionmentioning
confidence: 79%
“… Pairwise comparison Outlier position Candidate gene Candidate gene description Candidate gene function Native vs. Alice Springs ∩ Native vs. Pacific islands ∩ Native vs. all invasive NC_052499.1:51371013 LOC120775806 Sodium-coupled monocarboxylate transporter 1 Up-regulated in response to fluralaner insecticide in the common cutworm (Jia et al 2020 ); down-regulated at lower temperatures in in the red imported fire ant (Vatanparast et al 2021 ) Native vs. Alice Springs NC_052499.1:56113393 LOC120771435 Acetylcholinesterase Insecticide-targeted gene (Jia et al 2020 ); its expression was induced under temperature (heat) stress in honey bee workers (Kim et al 2019 ) Native vs. Alice Springs ∩ Native vs. all invasive NC_052499.1:56530119 LOC120782568 Protein timeless homologue Production of circadian rhythms including mating behaviour and diapause, involved in adaptation of such processes in response to changes in light and temperature (Tauber et al 2007 ) Native vs. Alice Springs NC_052499.1:75487809 LOC120782773 AN1-type zinc finger protein 6-like Important role in growth, aging and responses to biotic and abiotic stresses, e.g. environmental stresses that cause oxidative damage in vivo, such as heat, cold, UV light, and pesticides in Asian honey bee (Guo et al 2021 ) Native vs. Alice Springs ∩ Native vs. Pacific islands NC_052499.1:75635351 LOC120777560 Cadherin-99C Cadherin promotes cell adhesion and enhances cellular stability and integrity as a protective mechanism against heat stress in the thermophilic ant genus Cataglyphis (Perez et al 2021 ); confers resistance to Bt toxin in the cotton bollworm (Gao et al 2018 ) Native vs. Alice Springs ∩ Native vs. Pacific islands NC_052500.1:18467508 LOC120767202 Trehalose-phosphate phosphatase B Likely involved in thermotolerance in soldier flies (Stratiomyidae) larvae and stress resistance in other insects (Garbuz et al 2008 ) Native vs. Alice Springs NC_052501.1:9002087 LOC120770590 Ion transport peptide-like Encodes thirst-promoting and anti-diu...…”
Section: Resultsmentioning
confidence: 99%
“…ZFP41 is a type of ZFP, which play diverse roles in cell biological functions, such as cell differentiation, apoptosis, transcriptional regulation, cell metabolism and the immune response (45). current studies have found that ZFP41 plays a prominent role in tumor differentiation and oxidative stress, and is closely related to the co-expression of lacM and venous thromboembolism (46)(47)(48)(49). However, the role of ZFP41 in prognosis and cell function in Hcc has not yet been discovered.…”
Section: Discussionmentioning
confidence: 99%